Status Quo Perkawinan Beda Agama Pasca Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 - Antari, Putu Eva Ditayani; I Kadek Budiadinata Satriatama Adnyana; Luh Putu Yeyen Karista Putri (JUSTISI, 2025)
The trend of interfaith marriages is currently gaining interest in Indonesia. Data shows that by 2022, data on interfaith marriages will total 1425 spouses. The presence of the polemic about interfaith marriages in society has resulted in the government, through the Supreme Court, issuing SEMA 2/2023, which prohibits courts from accepting applications for interfaith marriages. Therefore, it is necessary to know the legality of interfaith marriages after SEMA 2/2023, especially regarding the legal ratio of the issuance of SEMA 2/20232. This study aims to determine the basis for the publication of SEMA 2/2023 and the validity of interfaith marriages after the publication of SEMA 2/2023. The study's novelty is demonstrated by the actuality of regulations published related to interfaith marriages in Indonesia, where previous studies analyzed the legality of interfaith marriages before the publication of SEMA 2/2023. The normative legal writing method is used by several approaches, such as the statutory regulations approach -invitation, case approach, and conceptual approach. The collection of legal materials in this study used literature study techniques. At the same time, the legal material analysis method is the descriptive analytical juridical method. The results show that the basis for preparing the circular letter is intended to guide judges in recording religious marriages in Indonesia. Also, since the circular letter came into force, the courts no longer have the authority to register interfaith marriages held in Indonesia.